Public-private research network / Suzaina Ismail - Ismail, Suzaina (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2018)
Department of Research, Indus-trial Linkages, Community & Alumni had organized a Public-Private Research Network (PPRN). PPRN is an innovative initiative of the Ministry of Higher Education of Malaysia to promote demand-driven innovation programmes in driving productivity im-provement of Small and Medium Enterprises (SMEs) and strength-ening Malaysia's economic development. The objective of PPRN is to create a knowledge-friendly ecosystem where knowledge is generated and dissemi-nated from those with knowledge and expertise at universities to the needy industries especially SMEs. Through this programme the industry players (SMEs) will present the issue on technology and explain the challenges in finding solu-tions. Hence, researchers from the universities will provide suggestions on how they can help the industry to address the problems and challenges based on their skills and expertise.